SPIRITUAL EDUCATION OF STUDENTS OF THE NEW UKRAINIAN SCHOOL IN WARTIME - Kopchuk-Kashetska, Maria; Tsiuniak, Oksana; Dovbenko, Svitlana (Mountain School of Ukrainian Carpaty, 2023)
The article analyzes the peculiarities of spiritual education of students in wartime within the framework of the New Ukrainian School. Taking into account the unpredictable challenges and stressful situations that manifest themselves in wartime, the methods and approaches aimed at forming spiritual resilience, patriotism and humanistic values among students are explored. The study emphasizes the importance of cooperation between school teachers, parents, and the public in shaping positive spiritual values of students during the war, which is of great importance for the future of Ukraine. The impact of the military conflict on the psychological state of students and their general well-being is analyzed. The article highlights the issues of incorporating modern technologies and interactive methods into the educational process, which improves the quality of spiritual education in the context of military conflict. In summary, the article offers a comprehensive approach to the spiritual education of students of the New Ukrainian School in wartime, taking into account the needs and characteristics of the modern school environment. Its results can be useful for teachers, administrative educational institutions, and all those interested in spiritual education and upbringing of young people in the context of military conflict.